GEOMEDIA FOR EDUCATION IN SUSTAINABLE DEVELOPMENT IN SPAIN. AN EXPERIENCE IN THE FRAMEWORK OF THE AIMS OF DIGITAL-EARTH.EU - Rafael de MIGUEL GONZALEZ (European Journal of Geography)
The use of geographic media in schools and teacher education is increasingly more important due to the growing number of geo-visualization tools. The present paper selects several maps obtained from the digital viewer SIU and from the data provided by the European project Corine Land Cover. Both express the cartography of the evolution in the occupation of land uses during the years 1987-2006 in the main metropolitan and urban Spanish areas, and therefore the growth of urban sprawl. However, this work does not only deal with the analysis and conclusion of urbanization processes, but also analyzes the benefits of using geographic media in geographic education, both to acquire competences for spatial thinking and educate on sustainable development.